2009
DOI: 10.1016/j.jacc.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Deficiencies

Abstract: Heart failure (HF) is a common, disabling, and costly disease. Despite major advances in medical therapy, morbidity and mortality remain high, in part because current pharmacological regimens may not fully address some unique requirements of the heart for energy. The heart requires a continuous supply of energy-providing substrates and amino acids in order to maintain its function. In HF, defects in substrate metabolism and cardiac energy and substrate utilization may contribute to contractile dysfunction. HF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(40 citation statements)
references
References 163 publications
0
38
0
Order By: Relevance
“…Metabolic strategies to treat heart disease were first proposed more than 50 years ago(35;36) and the literature has been recently reviewed(37;38). Another area where modest metabolic improvements may be clinically relevant in HF relates to the observation that fatty acid oxidation is increased in HF but is a less efficient carbon source than glucose, consuming 11–12% more oxygen per molecule of ATP synthesized(37;39).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic strategies to treat heart disease were first proposed more than 50 years ago(35;36) and the literature has been recently reviewed(37;38). Another area where modest metabolic improvements may be clinically relevant in HF relates to the observation that fatty acid oxidation is increased in HF but is a less efficient carbon source than glucose, consuming 11–12% more oxygen per molecule of ATP synthesized(37;39).…”
Section: Discussionmentioning
confidence: 99%
“…Soukoulis et al [28] and Marcovina et al [7] also reported that supplementation with L -carnitine improves the echocardiographic parameters due to better efficiency of mitochondrial function of cardiomyocytes. L -carnitine supplementation adjuvant treatment of HF showed an improvement in echocardiographic parameters [29,30], left ventricular dilatation attenuation [25] and 27% reduction of all cardiovascular causes of death [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to correct secondary muscle L -carnitine deficiency in patients with peripheral vascular disease, significantly improving walking capacity [25]. There have been several studies evaluating L -carnitine treatment in cardiovascular diseases and heart failure [26]. A multicenter trial CEDIM ( L -carnitine Ecocardiografia Digitalizzata Infarto Miocardico) showed a positive effect of L -carnitine on cardiac remodeling after myocardial infarction [27].…”
Section: Discussionmentioning
confidence: 99%